Creación del manual de identidad visual para la marca de compostura de prendas "Xirana" - Cristal Celeste, Huaira Perez (2022)
This project consists of the creation and realization of a visual identity manual for the Xirana brand, a clothing composition service. The objective of carrying out this project was to design a manual that brings together the strategic concepts of the brand, as well as its vision, in order to position it through a visual identity that reflects self-esteem and opportunity, in addition to the values of trust, empathy and commitment; all this through a coherent and differentiated communication from the competition. This purpose was validated by many design experts and included validation of the target audience. Likewise, it is proposed to establish a communication strategy that reflects the values of the brand in social networks.